Prevalence of Infection and Non-infection Complications in Continuous Ambulatory Peritoneal Dialysis in Tertiary Children Medical Centre - Tahir, Ali; Aldokhi, Mohamed Husein; Moghtaderi, Mastaneh; Bazargani, Behnaz; Abbasi, Arash; Fahimi, Daryoush; Askarian, Fahimeh; Basiry, Yasin (Journal of Pediatric Nephrology, 2025)
Background and Aim: Continuous ambulatory peritoneal dialysis (CAPD) is a conventional treatment for children with end-stage kidney disease. All infectious and non-infectious complications should be detected early and managed because they may cause ultrafiltration, or Soult failure, or catheter failure. This study aims to investigate infectious and noninfectious complications of CAPD, such as mechanical and metabolic issues, at a children’s medical center between 2020 and 2022. Methods: A retrospective cross-sectional study was performed on pediatric patients with end-stage renal disease (ESRD) undergoing peritoneal dialysis at Children’s Medical Center in 2020-2022. Data were collected from the medical records and files and entered into SPSS software, version 26 for analysis. Results: The study included 30 participants with an average age of 5.89±1.2 years. Twothirds of the participants were boys. Among the girls, 70% (7 of 10) and 80% of the boys (16 of 20) developed peritonitis. Bacterial infections were mostly observed in girls more than 2 times. Tunnel infections were observed in 10% of patients, three girls and one boy. Exit-site infection occurred in eight boys and one girl. Non-infectious complications, such as seizures, were observed in approximately 40% of patients. An inguinal hernia was observed in all male patients. Conclusion: In our experience, the most common infectious complication observed in CAPD patients was bacterial peritonitis caused predominantly by staphylococcus aureus. Tunnel infection and exit site infection were also common, while the predominant non-infectious complication was hernia.